2007
DOI: 10.1016/j.stem.2007.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 Expression Is Not Required for Mouse Somatic Stem Cell Self-Renewal

Abstract: The Pou domain containing transcription factor Oct4 is a well-established regulator of pluripotency in the inner cell mass of the mammalian blastocyst as well as in embryonic stem cells. While it has been shown that the Oct4 gene is inactivated through a series of epigenetic modifications following implantation, recent studies have detected Oct4 activity in a variety of somatic stem cells and tumor cells. Based on these observations it has been suggested that Oct4 may also function in maintaining self-renewal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
349
5
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 377 publications
(370 citation statements)
references
References 62 publications
12
349
5
4
Order By: Relevance
“…Importantly, NANOG also bound the Aurka promoter in keratinocytes (Fig. 5c), whereas it did not bind to an intronic Aurka region or to the Oct4 promoter, which is not active in somatic tissues 16 . As a positive control, we confirmed that NANOG binds the Oct4 promoter in ESCs (Fig.…”
Section: Sa-2xpamentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, NANOG also bound the Aurka promoter in keratinocytes (Fig. 5c), whereas it did not bind to an intronic Aurka region or to the Oct4 promoter, which is not active in somatic tissues 16 . As a positive control, we confirmed that NANOG binds the Oct4 promoter in ESCs (Fig.…”
Section: Sa-2xpamentioning
confidence: 93%
“…Upon implantation, Nanog, Oct4 and Sox2 expression is silenced in the majority of tissues. OCT4 is not expressed in normal adult tissues, but it is a driving oncogene in germ cell tumours 15,16 . SOX2 is expressed in adult neural stem cells 17 and in specific epithelia, notably including the oesophagus and forestomach, where it plays a role in tissue homeostasis 18 .…”
mentioning
confidence: 99%
“…In the adult, Oct4 is exclusively expressed in germ cells, and had been detected in stem-cell populations such as bone marrow multipotent adult progenitors, haematopoietic stem cells, and stem cells that reside in epidermal basal layers 78,79 . More recent studies demonstrate that OCT4 is essential for germ-cell maintenance, but dispensable for somatic stem-cell self-renewal 80,81 . The importance of strictly maintaining Oct4 expression levels has been demonstrated both in vitro and in vivo: even a two-fold change in OCT4 protein abundance can cause ES cells to lose pluripotency 82 , and ectopic Oct4 expression promotes epithelial dysplasia in transgenic mice 83 .…”
Section: Oct4 Regulation By O 2 Levelsmentioning
confidence: 99%
“…Some of these cells were described as expressing transcription factors characteristic for ESCs such as Octamer-4 (Oct-4). However, since the normal genome contains several Oct-4 pseudogenes, the real Oct-4 expression and its potential role in adult somatic cells requires further study (Lengner et al, 2007).…”
Section: Accumulating Evidence That Bm-derived Scs Are In Fact Heteromentioning
confidence: 99%